Spatial analysis of Bojnourd neighborhoods based on appropriate housing criteria - Rahimberdi Annamoradnejad; Mohamad Soleymani; Fatemeh Akbari (تحقیقات کاربردی علوم جغرافیایی)
Today, housing has found a concept beyond a shelter and plays an important role in how the physical quality of cities. In fact, one of the most important ways to know the status of housing in the housing planning process is to use housing indicators. These indicators, which indicate the quantitative and qualitative status of housing in any period of time, can be considered as a suitable guide to improve housing planning for the future. Therefore, the present study was conducted with the aim of leveling the neighborhoods of Bojnourd city based on housing indicators. The research is descriptive-analytical in nature and applied according to its purpose. The method of collecting information in the form of documents is library. In this study, 11 indicators related to housing quality were used to rank neighborhoods, and the Waspas model was used to rank neighborhoods. The statistical population of the study includes 42 neighborhoods of Bojnourd. Based on the results, it was found that half of the neighborhoods (22 neighborhoods) of Bojnourd  are in a favorable and completely desirable housing condition, in contrast to 28% of the city neighborhoods are in a relatively favorable condition that the number of population at this level is equal to It is 31% of the total population of the city. Finally, there is the unfavorable housing situation, which includes 8 neighborhoods of the city. The total population of these neighborhoods is equal to 17% of the city's population, which is located in an area of ​​973 hectares.